Structure And Performance of The Services Sector In Transition Economies - Fernandes, Ana Margarida 2002- (The World Bank, 2007)
This paper examines the structure and performance of the services sector in Eastern European and Central Asian countries during 1997-2004. Services represent an increasing share of total value added and employment with the major sub-sectors being wholesale trade, retail trade, inland transport, telecommunications, and real estate activities. A clear divide separates EU-5 countries from South Eastern European countries and Ukraine in terms of services labor productivity. Although a large gap in productivity also separates EU-8 countries from EU-15 countries, that gap was reduced from 1997 to 2004 as most services sub-sectors experienced fast productivity growth. High skill intensive sub-sectors and information and communications technology producers and users have exhibited higher productivity levels and growth rates relative to other sub-sectors since 2000. The author finds a positive effect of services liberalization on the productivity growth of services sub-sectors. The author also finds a positive and significant effect of services liberalization in both finance and infrastructure on the productivity of downstream manufacturing